Respuesta :

First you have to replace each F(x) or functions like that with y. Then you swap the x (in some of your functions n) with the y. Step number three is to solve for y.

10. y=2x^5 -1

x = 2y^5 - 1

x + 1 = 2y^5

(x + 1) / 2 = y^5

[ ( x + 1 ) / 2 ] ^1/5 = y or all of the answer in brackets underneath a with the number 5

You then replace the y that is all by itself with the f^-1(x) or n

11. y = ( -5n + 20 ) / 2

12. y = - (x/2)^1/3 do the same thing as before and put it under a radical with the number three with the negative on the outside

13. y = -3n + 4

14. y = x^3 - 1

Ver imagen kikiwahl00